The efficacy and safety of sacubitril/valsartan compared with ACEI/ARB in the treatment of heart failure following acute myocardial infarction: a systematic review and meta-analysis of randomized controlled trials - Gao, Jinquan; Zhang, Xin; Xu, Mengzhuo; Deng, Shisu; Chen, Xiaoping (Frontiers in Pharmacology, 2023)
Purpose: To systematically assess the efficacy and safety of sacubitril/valsartan (SV) by comparison with angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) for the treatment of heart failure caused by acute myocardial infarction (HF-AMI) based on current randomized controlled trials (RCTs). Methods: Several electronic databases were searched up to 27 May 2023. Primary endpoints were the efficacy including the left ventricular ejection fraction (LVEF), left ventricular end-diastolic diameter (LVEDD), N-terminal pro-B type natriuretic peptide (NT-proBNP) and 6-min walk test (6MWT) and secondary endpoints were the safety including the major adverse cardiovascular event (MACE) and adverse reaction (AE). Results: A total of 14 RCTs were included and all patients were from China. Among included 1,991 patients, 997 patients received SVs and 994 patients received ACEIs/ARBs. The pooled results demonstrated that patients in the SV group showed significantly better efficacy representing as increased LVEF [weighted mean difference (WMD): 4.43%, 95% confidence interval (CI): 2.84%–6.02%, p < 0.001] and 6MWT (WMD: 30.84 m, 95% CI: 25.65 m–36.03 m, p < 0.001) and decreased LVEDD (WMD: −3.24 mm, 95% CI: −4.96 mm ∼ -1.52 mm, p < 0.001) and NT-proBNP (WMD: −188.12 pg/mL, 95% CI: −246.75 pg/mL ∼ 129.49 pg/mL, p < 0.001), which was also verified by subgroup analysis based on the history of percutaneous coronary intervention (PCI). Besides, the SV group showed significantly lower incidence rate of MACE [relative risk (RR): 0.60, 95% CI: 0.47–0.75, p < 0.001] and patients receiving SVs in the non-PCI group also showed lower incidence of AE (RR: 0.38, 95% CI: 0.20–0.71, p = 0.002). Conclusion: For the treatment of HF-AMI, SV is more effective and safer than ACEI/ARB based on current evidence, but more high-quality RCTs are still needed to verify above findings.